A Slave Ship Called Jesus - Ogun, Dele (Nigeria, 2021)
This book offers answers to many questions surrounding the slave trade: Why did England join a trade which it had previously spurned as immoral? How did the Church and medieval society reconcile their abhorrence of usury with the exploitation of slavery? Why were slave ships given names of like 'Jesus of Lubeck' and 'Grace of God'? How did a slave trader come to write the hymns 'How sweet the name of Jesus sound?' and 'Amazing Grace'?...
Keywords: Non-Fiction; Slave Trade; Slavery